PENGOLAHAN IKAN ASAP LELE DUMBO MENGGUNAKAN ASAP CAIR DALAM PENGAWETAN HASIL PERIKANAN - Pangesti, Ita Diah; Wiharto, Muhammad; Patang, Patang (Jurnal Pendidikan Teknologi Pertanian, 2017)
This study aims to determine the effect of the addition of liquid smoke concentration to the chemical properties of dumbo catfish fish and to determine the level of panelist acceptance of the organoleptic value of the resulting dumbo catfish fish. This research is a quantitative research (experiment) using Randomized Complete Design (RAL) with variation of liquid smoke concentration 0%, 6%, 8% and 10%. At fogging 4 hours with temperature 60 â„ƒ. Parameters observed included moisture content, fat content, protein content, phenol content, TBA and organoleptics including flavor, aroma, color, and texture. The data obtained will be analyzed by analysis of variance (ANOVA) and Duncan's advanced test. The results showed that smoked dumbo catfish using liquid smoke most favored by panelists was Dumbo catfish smoke which was produced at 10% liquid smoke concentration treatment.